2013
DOI: 10.1177/0091270011433327
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm to Detect Adverse Drug Reactions in the Neonatal Intensive Care Unit

Abstract: Critically ill newborns in neonatal intensive care units (NICUs) are at greater risk of developing adverse drug reactions (ADRs). Differentiation of ADRs from reactions associated with organ dysfunction/immaturity is difficult. Current ADR algorithm scoring was established arbitrarily without validation in infants. The study objective was to develop a valid and reliable algorithm to identify ADRs in the NICU. Algorithm development began with a 24-item questionnaire for data collection on 100 previously suspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 39 publications
0
65
0
Order By: Relevance
“…Neonatal pharmacovigilance has been described (114). Du et al have outlined and tested a method for evaluation of the relation of an adverse event to the administration of a medication (115). They developed a classification of the relation to the medicinal product as definite, probable, possible or unlikely based on the following 13 criteria:…”
Section: Adverse and Serious Adverse Event Reportingmentioning
confidence: 99%
“…Neonatal pharmacovigilance has been described (114). Du et al have outlined and tested a method for evaluation of the relation of an adverse event to the administration of a medication (115). They developed a classification of the relation to the medicinal product as definite, probable, possible or unlikely based on the following 13 criteria:…”
Section: Adverse and Serious Adverse Event Reportingmentioning
confidence: 99%
“…As a recent illustration, we refer to the evaluation of the use of uncoated mini-tablets instead of syrup for neonates. Uncoated mini-tablets offer the potential of a single formulation for different age groups and [5,6,10,11,13,15], and pharmacovigilance [7,8] in neonates, but should also shift towards medicines and product development driven by neonatal pathophysiology [9] avoid the need for specific excipients or taste-masking compounds [10,15].…”
Section: Neonatal Clinical Pharmacy: How To Cope With Neonatal Formulmentioning
confidence: 99%
“…However, once a signal has been detected, the differentiation of Btrue^ADRs from confounding events associated with immaturity, organ dysfunction, or underlying diseases remains difficult. An algorithm as suggested by Du et al based on 13 questions tailored to neonates has been shown to be more reliable when compared to the Naranjo approach [8].…”
Section: Neonatal Clinical Pharmacy: How To Cope With Neonatal Formulmentioning
confidence: 99%
“…Methods to ascertain the causal relationship between an intervention and an adverse event have been proposed [77]. Causality assessment can be difficult at the level of individual babies.…”
Section: Safety Reportingmentioning
confidence: 99%